Selective Inhibition of HER2-Positive Breast Cancer Cells by the HIV Protease Inhibitor Nelfinavir - Shim, Joong Sup (Oxford University Press, 2012)
BACKGROUND: Human epidermal growth factor receptor 2 (HER2)–positive breast cancer is highly aggressive and has higher risk of recurrence than HER2-negative cancer. With few treatment options available, new drug targets specific for HER2-positive breast cancer are needed. METHODS: We conducted a pharmacological profiling of seven genotypically distinct breast cancer cell lines using a subset of inhibitors of breast cancer cells from a screen of the Johns Hopkins Drug Library. To identify molecular targets of nelfinavir, identified in the screen as a selective inhibitor of HER2-positive cells, we conducted a genome-wide screen of a haploinsufficiency yeast mutant collection. We evaluated antitumor activity of nelfinavir with xenografts in athymic nude mouse models (n = 4–6 per group) of human breast cancer and repeated mixed-effects regression analysis. All statistical tests were two-sided. RESULTS: Pharmacological profiling showed that nelfinavir, an anti-HIV drug, selectively inhibited the growth of HER2-positive breast cancer cells in vitro. A genome-wide screening of haploinsufficiency yeast mutants revealed that nelfinavir inhibited heat shock protein 90 (HSP90) function. Further characterization using proteolytic footprinting experiments indicated that nelfinavir inhibited HSP90 in breast cancer cells through a novel mechanism. In vivo, nelfinavir selectively inhibited the growth of HER2-positive breast cancer cells (tumor volume index of HCC1954 cells on day 29, vehicle vs nelfinavir, mean = 14.42 vs 5.16, difference = 9.25, 95% confidence interval [CI] = 5.93 to 12.56, P < .001; tumor volume index of BT474 cells on day 26, vehicle vs nelfinavir, mean = 2.21 vs 0.90, difference = 1.31, 95% CI = 0.83 to 1.78, P < .001). Moreover, nelfinavir inhibited the growth of trastuzumab- and/or lapatinib-resistant, HER2-positive breast cancer cells in vitro at clinically achievable concentrations. CONCLUSION: Nelfinavir was found to be a new class of HSP90 inhibitor and can be brought to HER2-breast cancer treatment trials with the same dosage regimen as that used among HIV patients.